The role of CD36 in immune function: bridging innate and adaptive responses - Zhang, Xiang; Luo, Ling-jie; Wu, Yan-wei; Chen, Liang (Frontiers in Immunology, 2026)
CD36 is a multifunctional glycoprotein essential in fatty acid metabolism, angiogenesis, and atherogenesis, playing a critical role in immunological processes. This comprehensive review synthesizes current research to elucidate CD36’s integral functions within the immune system, including its involvement in phagocytosis, inflammation, and the crucial interplay between innate and adaptive immune responses. We highlight novel insights into CD36 as a therapeutic target, presenting recent advances in targeting strategies for a spectrum of conditions such as inflammatory diseases, infections, metabolic disorders and cardiovascular diseases. By evaluating emerging research and clinical trials, this review proposes innovative approaches for exploiting CD36’s therapeutic potential, aiming to inspire further research and development in disease treatment.